Propuesta arquitectónica de un parque recreacional con un sistema de aguas residuales en la ciudad de Guayaquil - León Moran, Geraldine Nicole (2023)
In summary, the Architectural Proposal for a Recreational Park with a Sanitation System in Guayaquil pursues the transformation of water use and management in various architectural elements, such as bathrooms, water games, fountains, among others. In addition, it emphasizes the importance of environmental sustainability and community well-being. The study addresses the excessive water consumption associated with the maintenance of recreational areas. It´s evidence on the lack of parks in Lomas de la Florida that promote sports, respect for nature and water awareness. The results obtained through surveys highlight the lack of recreational spaces and the absence of territorial planning in the area. The aim is to enrich the urban image of the sector through an innovative and sustainable design. The effectiveness of the project places it as a reference in the conception of recreational areas and the conservation of water resources.